Acetabular Bone Density and Metal Ions after Metal-On-Metal versus Metal-On-Polyethylene Total Hip Arthroplasty; Short-Term Results. Issue 2 (March 2014) - Zijlstra, Wierd P.; van der Veen, Hugo C.; van den Akker-Scheek, Inge; Zee, Mark J.M.; Bulstra, Sjoerd K.; van Raay, Jos J.A.M.
Information on periprosthetic acetabular bone density is lacking for metal-on-metal total hip arthroplasties. These bearings use cobalt-chromium instead of titanium acetabular components, which could lead to stress shielding and hence periprosthetic bone loss. Cobalt and chromium ions have detrimental effects on bone. It is unknown whether serum metal ion levels affect bone density clinically. We compared cementless large femoral head (mean 48 mm) metal-on-metal total hip arthroplasties (M2a-Magnum, Biomet) to cementless 28 mm metal-on-polyethylene total hip arthroplasties (Mallory-Head, Biomet) in a randomised clinical trial. We evaluated periprosthetic acetabular bone density and serum metal ion levels at 1 year postoperatively. Acetabular bone density was analyzed with dual energy x-ray absorptiometry in four horizontal regions of interest in 70 patients. After one year, acetabular bone density decreased (-3.5% to −7.8%) in three of four regions of interest in metal-on-polyethylene patients, but was retained in metal-on-metal patients. Bone density preservation was most pronounced superior to the metal-on-metal cup (+1% versus −3.7%). Serum cobalt, chromium and titanium ion levels were not related to bone density, nor to acetabular inclination or femoral head size. Oxford and Harris hip scores were similar in both groups. Contrary to our hypothesis, acetabular bone density was retained with metal-on-metal total hip arthroplasty, compared to metal-on-polyethylene arthroplasty. Bone preservation was most pronounced in the area superior to the cup. This could be a benefit during future revision surgery.